How to reduce the potential risk of vertical transmission of SARS-CoV-2 during vaginal delivery?. (July 2020) - Carosso, Andrea; Cosma, Stefano; Serafini, Paola; Benedetto, Chiara; Mahmood, Tahir
Abstract: The risk of vertical transmission during vaginal delivery in COVID-19 pregnant patients is currently a topic of debate. Obstetric norms on vaginal birth assistance to reduce the potential risk of perinatal infection should be promoted by ensuring that the risk of contamination from maternal anus and faecal material is reduced during vaginal delivery.